Pfs230 and Pfs48/45 Fusion Proteins Elicit Strong Transmission-Blocking Antibody Responses Against Plasmodium falciparum - Singh, Susheel K.; Thrane, Susan; Chourasia, Bishwanath K.; Teelen, Karina; Graumans, Wouter; Stoter, Rianne; van Gemert, Geert-Jan; van de Vegte-Bolmer, Marga G.; Nielsen, Morten A.; Salanti, Ali; Sander, Adam F.; Sauerwein, Robert W.; et al. (Frontiers in Immunology, 2019)
The Plasmodium falciparum Pfs230 and Pfs48/45 proteins are expressed during transmission from man to mosquito and are leading candidates for a malaria transmission blocking vaccine. Individually they generate transmission blocking (TB) antibodies in rodent models. Whether the single protein vaccines are suitable to use in field settings will primarily depend on their potency to elicit functional antibodies. We hypothesized that a combination of both proteins will be more potent than each protein individually. Therefore we designed chimeric proteins composed of fragments of both Pfs230 and Pfs48/45 as well as single protein fragments, and expressed these in Lactoccus lactis. Both the individual Pfs230 and Pfs48/45 fragments and chimeras elicited high levels of functional antibodies in mice. Importantly, one of the chimeric proteins elicited over threefold higher transmission blocking antibody responses than the single antigens alone. Furthermore the immunogenicity of one of the chimeras could be enhanced through coupling to a virus-like particle (VLP). Altogether these data support further clinical development of these novel constructs.